Development of hybrid kenaf-glass reinforced UPE composite for structural applications - Atiqah binti Mohd Afdzaluddin (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
Hybrid synthetic and natural fiber composite materials are attractive structural materials because of natural fibers resource and their lower cost. Hybrid composite materials have been dominant emerging materials in engineering field. The demand of new materials for structural applications is increasing due to recent advances in construction, automobile, household, military structure and other industries. In this work, hybrid kenaf-glass (KG) reinforced unsaturated polyester (UPE) resin composite was selected as the most appropriate material for new generation structural application using digital logic (DL) and knowledge based system (KBS) methods. Sheet moulding compound (SMC) method was used to develop hybrid kenaf and glass by varying the volume of kenaf and glass fibers starting from 0%, 7.5%, 15%, 22.5% and 30% in UPE matrix coded with 30 GF, 7.5/22.5 KG, 15/15 KG, 22.5/7.5 KG and 30 KF respectively. This study covered the effect of mercerization on kenaf fiber and electron beam radiation of 75 kGy doses on the fabricated hybrid composites. The mechanical properties of developed hybrid kenaf-glass composite reinforced UPE composite were studied through flexural, tensile and impact tests. The thermal properties were characterized using thermagravimetric analysis (TGA) and dynamic mechanical analysis (DMA) methods. The morphology of the hybrid composites were studied by scanning electron microscopy (SEM). Furthermore, fourier transform infra-red (FTIR) analysis was carried out to distinguish the treated and untreated kenaf fiber and irradiated and non-irradiated of electron beam (EB) radiation on developed hybrid composites. The mercerization treatment of kenaf fiber caused a great influence towards the mechanical properties of hybrid KG-UPE composite and also higher when treated kenaf fiber in the hybrid formulations. Among the five formulations the 15/15 KG with treated kenaf showed optimum formulation with higher, tensile and impact strength. Conversely, the effect of electron beam radiation lowers the flexural and tensile strength but increases the impact strength and water uptake significantly. In fracture surface, the morphology of kenaf treated hybrid composite shows less matrix cracking, smoother matrix surface and less fiber debonding compared to untreated kenaf in the hybrid formulations. The impact strength of irradiated 15/15 KG composite showed higher impact energy with the value of 180.33 kJ/m² at room temperature compared to +50 °C and -50 °C impact tested composites with the values of 131.33 kJ/m² and 155.52 kJ/m² respectively. The thermal properties of irradiated hybrid composites showed the decreasing trend of dynamic storage modulus and loss modulus with increasing kenaf fiber in the hybrid formulations. However, 15/15 KG-UPE composite showed moderate range of storage modulus and loss modulus with increasing temperature. These in turns, increased the energy dissipation factor (tan δ) of the hybrid composites. Conclusively, hybrid 15/15 KG composite showed better thermomechanical properties which can be recommended for structural applications.